Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Chapter 11 - Sequences; Induction; the Binomial Theorem - Chapter Review - Review Exercises - Page 859: 18



Work Step by Step

The $n^{th}$ term of a geometric sequence is given by the formula: $a_n = a_1 \ r^{(n-1)}(1)$ where, $a_1 = \ First \ Term$ and $r=\dfrac{a_2}{a_1}= \ Common \ Ratio$ We have: $a_1=1 $ and $r=\dfrac{a_2}{a_1}=\dfrac{1/10}{1} =\dfrac{1}{10}$ Plug in $11$ for $n$ into equation (1) to obtain: $a_{11} = (1) \times (\dfrac{1}{10})^{(11-1)}=(\dfrac{1}{10})^{10}=10^{-10}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.